The social experiences of older adults in serviced apartments : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Palmerston North, New Zealand - Hajdu, Jodie (Massey University, 2022)
The focus of this study was to understand the social lives of older adults living in serviced apartments. As an increasingly available housing option within the growing retirement village lifestyle market, serviced apartments are an unexplored area for social research in New Zealand. To support this inquiry participants were recruited from two retirement villages providing serviced apartment in the Nelson/Tasman region. Seven participants responded, including four females and three males. Individual semi-structured interviews were conducted asking participants about their social lives and how shifting into a serviced apartment had impacted on their social worlds. Three themes emerged relating to social networks, participation in activities, and dependency. Participants talked of their meaningful interactions with old friends and regular contact with family members, who are important areas of practical and emotional support. Residents often visited their friends outside their home, while their apartments were used as a place to rest and be alone. The activities offered by the retirement villages are multiple and cater to the interest of participants, who resorted to these options when community activities were no longer accessible. The impact of physical decline and loss of transport increased dependency on the retirement villages to provide assistance and access to the community. These findings were supported by the literature and provided support for two major theories of adaptation to ageing. The implications of this research suggest a risk for loneliness among new serviced apartment residents without previous connections to residents within the retirement villages, and a loss of in-person contact with friends as physical decline limits residents’ ability to participate. The thesis concludes that, overall, participants are satisfied with their social lives and are able to adapt to changes in their physical abilities in ways that aim to maintain meaningful social interaction and participation.
Keywords: 520304 Health psychology